Application of the Emilia Reggio Approach (Rea) Assisted by Flash Card Media to Improve the Mastery of Indonesian Vocabulary in Children Ages 5 to 6 Years - Sindrayuni, Dian; Sastromiharjo, Andoyo; Mulyati, Yeti; Damaianti, Vismaia (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This study aims to improve the mastery of Indonesian vocabulary in early childhood 5-6 years in TK Kartina Garut Regency. The focus of his research is on the application of the Reggio Emilia Approach (REA) assisted by flash card media to improve the mastery of Indonesian vocabulary in early childhood 5-6 years. This research is in the form of Classroom Action Research (CAR) with the aim of improving or increasing vocabulary mastery in early childhood. The analysis shows that this media is useful to be used as an introduction to the mastery of Indonesian children's vocabulary. The percentage increase in mastery of Indonesian vocabulary before action / pre-cycle was 49.44%, cycle I 61.94%, cycle II 77.22%, and cycle III 86.94%. Increased mastery of Indonesian vocabulary through flash card, namely mastery of Indonesian vocabulary in group B children in TK Kartina. The child can mimic some Indonesian vocabulary, mention the name of the object shown, and show some of the pictures requested. Teachers are more creative in conveying learning because by using flasch cards they are more motivated to increase all scope of development by using attractive media according to the teacher's creation